Charles Wright Mills Dan Teori Power Elite: Membaca Konteks Dan Pemetaan Teori Sosiologi Politik Tentang Kelas Elite Kekuasaan - Ahmad Imam Mawardi (Faculty of Social Science, Universitas Negeri Malang, 2019)
This study aims to explain the paradigm of power elite theory by Charles Wright Mills (C. Wright Mills, henceforth) in relation to the context of mapping the political sociology theory of the elite class in the United States. The method employed in this study was library research. Based on the literature review, it is concluded that three groups of political elites in the United States according to C. Wright Mills controlled the political and power arena consisting of the bureaucratic elite, business elite, and military elite. Second, the middle and lower classes are often exploited in the interests of the elite in politics and struggle for class power in the United States. Genealogical and other external factors greatly influence the birth and development of elite power generation in the United States. The theory is eventually in contact with the theory of pluralism that has long-lived among American societies. This literature study can be a catalyst showing how political theories and sociology compete each other to seize dominance in the political and social arena, especially in a developed country like the United States.